Environmental Politics in the Implementation of Waste Management: A Study of the Environment Agency of West Lampung Regency - Yandi Rianto Ramadhan; Ali Abdul Wakhid; Gesit Yudha (UIN Mataram, 2026)
This study examines the role of environmental politics in the implementation of waste management by the West Lampung Regency Environmental Agency (DLH). The volume of waste that reaches around 120 tonnes per day, with only 70% effectively managed, presents a critical governance challenge. Using Piers Blaikie's theory of Political Ecology, this qualitative field research was conducted through in-depth interviews, participatory observation, and documentation analysis. The findings of the study show that although DLH has a clear regulatory foundation, especially Regional Regulation Number 15 of 2013 and Regent Regulation Number 48 of 2018, its implementation faces significant obstacles. These obstacles include infrastructure limitations such as lack of adequate landfills and transport fleets, inadequate budget allocation for operations and maintenance, uneven distribution of waste services between sub-districts (some remote areas are unreachable), and low community participation which only reaches 35% in sorting activities and levy payments. This low participation is exacerbated by weak environmental awareness and lack of strict sanctions. This study concludes that strengthening DLH's institutional capacity, increasing regional budget commitments in a sustainable manner, and developing participatory and ecologically fair community involvement are absolute requirements to achieve sustainable waste management in West Lampung. On top of these three pillars, the gap between policy and practice will continue to widen, threatening the environment and social justice.